2021
DOI: 10.1111/1365-2745.13635
|View full text |Cite
|
Sign up to set email alerts
|

Biomass partitioning in response to intraspecific competition depends on nutrients and species characteristics: A study of 43 plant species

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 133 publications
(163 reference statements)
4
33
0
Order By: Relevance
“…Resource limitations are important traits of many biodiversity studies that reveal increased productivity during genotype mixtures [68][69][70]. Indeed, context dependency is an important concept in biodiversity research [11,71]. More research is needed under resource-limited conditions to determine if the improvement in Serianthes root growth by stranger root contact is greater than in our study, for example in natural field conditions e.g., [72].…”
Section: Future Directionsmentioning
confidence: 82%
“…Resource limitations are important traits of many biodiversity studies that reveal increased productivity during genotype mixtures [68][69][70]. Indeed, context dependency is an important concept in biodiversity research [11,71]. More research is needed under resource-limited conditions to determine if the improvement in Serianthes root growth by stranger root contact is greater than in our study, for example in natural field conditions e.g., [72].…”
Section: Future Directionsmentioning
confidence: 82%
“…malviflora , and S . pulchra suggests that belowground resources may be more limiting than light or aboveground space for these California coastal grassland species (Bloom et al, 1985 ; Poorter et al, 2012 ; Rehling et al, 2021 ). Aside from biomass allocation, we found certain species adjusted functional traits in response to competition.…”
Section: Discussionmentioning
confidence: 99%
“…Water‐limited plants have been shown to partition growth more so to root than shoot structures (Liu & Stützel, 2004 ). Biotic stressors such as competition can have more varied impacts because it unevenly interacts with abiotic resources, which is further complicated by species‐specific responses (Rehling et al, 2021 ). Invasive competition could lead to increased allocation to shoots or leaves to increase access to space and light (Pérez‐Harguindeguy et al, 2016 ; Westoby, 1998 ), or increased allocation to roots to access limiting belowground resources, especially in abiotically harsh systems (Liu & Stützel, 2004 ; Poorter et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we can pinpoint several arguments explaining that simple allometric effects can also be at stake. Several studies have reported that most grass species have an allometric coefficient α lower than 1 (their M R :M S decreases as a plant grows) 13 , 46 , possibly to compensate for a lower nitrogen uptake per root mass 47 , 48 . In this situation, the higher the decrease of the growth rate, the higher the increase of the M R :M S ratio due to allometric effects (see Fig.…”
Section: Discussionmentioning
confidence: 99%